Product Distribution Route Optimization Using The Traveling Salesman Problem (Tsp) Method At Pt. Inbisco Niagatama Semesta (Mayora Group) In Makassar - Kharisma, Mizna Laila; Ahmad, Arfandi; Malik, Rahmaniah (Journal of Industrial System Engineering and Management, 2024)
In industry, the effective use of distribution channels is a key factor in reducing transportation costs. This research aims to optimize the product distribution routes of PT. Inbisco Niagatama Semesta (Mayora Group) using the Traveling Salesman Problem (TSP) Method. Product distribution is an important element in the supply chain, and this research can help improve operational efficiency and reduce company costs. Companies face various challenges such as variations in distribution quantities, capacity constraints, tight delivery times, and demand fluctuations. By analyzing distribution data, this research aims to find optimal distribution routes that minimize travel distance and distribution costs. The results of this research show that the shortest route obtained from calculations using the traveling salesman problem branch and bound method of WinQsb software obtained distribution delivery route results that had been calculated with a total distance of 88.40 km with a predetermined delivery route and obtained a total travel time of 132. 6 minutes and fuel consumption at a cost of Rp. 60.112